Development of 20(S)-Protopanaxadiol-Loaded SNEDDS Preconcentrate Using Comprehensive Phase Diagram for the Enhanced Dissolution and Oral Bioavailability - Young Hoon Kim; Yu Chul Kim; Dong-Jin Jang; Kyoung Ah Min; Jenisha Karmacharya; Thi-; Han-Joo Maeng; Kwan Hyung Cho (MDPI AG, 2020)
In this study, we aimed to develop a 20(S)-protopanaxadiol (PPD)-loaded self-nanoemulsifying drug delivery system (SNEDDS) preconcentrate (PSP) using comprehensive ternary phase diagrams for enhanced solubility, physical stability, dissolution, and bioavailability. Capmul MCM C8 and Capryol 90 were selected as the oil phase owing to the high solubility of PPD in these vehicles (>15%, w/w). Novel comprehensive ternary phase diagrams composed of selected oil, surfactant, and PPD were constructed, and the solubility of PPD and particle size of vehicle was indicated on them for the effective determination of PSP. PSPs were confirmed via particle size distribution, physical stability, and scanning electron microscope (SEM) with the dispersion of water. The optimized PSP (CAPRYOL90/Kolliphor EL/PPD = 54/36/10, weight%) obtained from the six possible comprehensive ternary phase diagrams showed a uniform nanoemulsion with the particle size of 125.07 ± 12.56 nm without any PPD precipitation. The PSP showed a dissolution rate of 94.69 ± 2.51% in 60 min at pH 1.2, whereas raw PPD showed negligible dissolution. In oral pharmacokinetic studies, the PSP group showed significantly higher Cmax and AUCinf values (by 1.94- and 1.81-fold, respectively) than the raw PPD group (p < 0.05). In conclusion, the PSP formulation with outstanding solubilization, dissolution, and in-vivo oral bioavailability could be suggested using effective and comprehensive ternary phase diagrams.